ИССЛЕДОВАНИЕ ПИТАНИЯ И МОРФОФИЗИОЛОГИЧЕСКИХ ИНДИКАТОРОВ РЫБ РОДА SPICARA - (:unkn) unknown (Киев : Наукова думка, 1980)
Рассмотрено питание трех видов рыб рода Spicara — S. flexuosa (спикара), S. maena (мэнола) и S. smaris (смарида) — в морях Средиземноморского бассейна. Приведены данные по качественному составу пищи каждого вида. Определены коэффициенты вариации длины и массы тела спикары, индексы печени и селезенки, упитанность. Данные характеристики исследованы у рыб разного пола, возраста и района обитания. Полученные результаты позволяют предположить, что спикара в разных частях ареала образует локальные популяции, отличающиеся спектром питания, изменчивостью длины и массы, упитанностью, индексом печени и селезенки.
Studies in nutrition and morphophysiological indicators of the genus Spicara fishes
Three fish species of the genus Spicara inhabiting the Mediterranean Sea basin: S. flexuosa Raf., S. maena (L.) and S. smaris (L.), are considered from the point of view of their nutrition. Data on food qualitative composition are presented for each species, with a large number of plankton and benthos organisms being involved. Their importance in the food is different for different species and is dependent on the season and region for each species. The coefficient of variation in the S. flexuosa Raf. body length and mass, the liver and spleen indices, fatness are evaluated. The given characteristics are studied in fishes of different sex, age and regions, in different parts of the area of distribution the S. fexuosa Raf. forms local populations differing in the nutrition spectrum, variability in length and mass, fatness, the liver and spleen indices.